Saberes, vivência e ancestralidade: dinâmicas de aprendizados e continuidade nas práticas de curas entre benzedeiro(a)s e curandeiro(a)s de Monte Alegre – PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
In the Amazon we have an expressive number of healers, faith healers, handlers, shamans, midwives, fathers a nd mothers of saints, who are very important personalities for those who seek spiritual help. Healers and healers are recognized for the work with medicinal herbs and prayers that were passed on to them during their process of initiating healing practices. This dynamic of transfers takes place through the enchanted caboclos, by people close to them or revelations. Therefore, this Course Conclusion Work aimed to carry out an analysis of the dynamics of healing practices and learning through the hands of healers of African origin religion, in the city of Monte Alegre-PA and to understand how these practices occur in the lives of people who are starting this activity, especially as the older ones are thinking about the interest of the younger ones. In addition to talking about how the process of transmission of knowledge takes place with those who are starting in the field of healing and blessing. The methodology developed was to carry out oral history and ethnography with the research interlocutors, who are references in the field of healing and blessing in the city of Monte Alegre, being Maria Guiomar, Lindalva Borges, Ubiraci Pinon, Pai Jackson Valente, Maria da Conceição and Little Father Kisse Leivas. It is, therefore, a work on the dynamic processes of sharing the know-how of healers and healers. and ancestors. As a result, I noticed a strong performance of the younger ones who are in a constant learning process, as relationships are established with the older ones, the learning dynamics become continuous in relation to healing practices. I also emphasize that the process of learning and initiation between the interlocutors are similar and form a web of relationships that involve symptoms in the body with the manifestation of entities, ancestral strength and inspiration from the elders. Just like the gira, which messes with our bodies and has no end, it is just pulled over and is on the lookout for the next beginning, the teaching-learning process between healers and faith healers is like a cycle that is being passed on between generations and involves body and ancestry.
Keywords: Transmissão de saberes; Práticas de cura; Benzimento; Religiões de Matriz Africana; Amazônia; CNPQ:: CIÊNCIAS HUMANAS